Effect of cold rolling on the corrosion behavior of Ta-4W alloy in sulphuric acid. (November 2020) - Ma, Guoqiang; Wu, Guilin; Shi, Wei; Xiang, Song; Chen, Qiang; Mao, Xinping
Graphical abstract: Highlights: With increasing strain, the corrosion resistance of Ta-4%W first decreases and then increases. The 90% cold rolled sample has a better corrosion resistance than the initial annealed sample. The development of γ-texture enhanced greatly the corrosion resistance of the 90% cold rolled sample. The strong γ-texture is believed to be the mainly reason for the greatly enhanced corrosion resistance of the 90 % cold rolled sample. Abstract: The effect of cold rolling on the corrosion behavior of Ta-4%W in sulphuric acid was investigated. The results demonstrated that cold rolling deformation has a two-side effect on the corrosion resistance of the alloy. Low to intermediate strained rolling deformation (10 %–50 % reductions in thickness) is detrimental to the corrosion resistance due to the increased dislocations during the rolling process; while high strained rolling deformation (70 % and 90 % reductions in thickness) enhances the corrosion resistance caused by the formation of textures (preferential crystallographic orientations). The 90 % cold rolled sample shows a greatly enhanced corrosion resistance even better than the initial annealed sample.